Efficacy of orally disintegrating film of ondansetron versus intravenous ondansetron in prophylaxis of postoperative nausea and vomiting in patients undergoing elective gynaecological laparoscopic procedures: A prospective randomised, double-blind placebo-controlled study - Hegde, Harihar V (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND AND AIMS: Ondansetron is one of the most widely used drugs for postoperative nausea and vomiting (PONV) prophylaxis. Orally disintegrating film (ODF) formulations are relatively recent innovations. We evaluated the efficacy of ODF of ondansetron for the prophylaxis of PONV. METHODS: One hundred and eighty American Society of Anaesthesiologists-I or II women, in the age group 18-65 years, scheduled for elective gynaecological laparoscopic procedures were studied in a prospective randomised, double-blind, placebo-controlled trial. The patients were randomised into four groups: Placebo, intravenous (IV) ondansetron 4 mg, ODF of ondansetron 4 mg (ODF4) and 8 mg (ODF8) groups. PONV was assessed in two epochs of 0-6 and 7-24 h. Primary outcome measure was the incidence of PONV and secondary outcome measures were severity of nausea, need for rescue anti-emetic, analgesic consumption, time to oral intake, overall patient satisfaction and side effects such as headache and dizziness. PONV was compared using analysis of variance or Mann–Whitney U-test as applicable. RESULTS: Data of 173 patients were analysed. The incidence of postoperative nausea was significantly lower (P = 0.04) only during the 0-6 h in the ODF8 group when compared with the placebo group. During the 0-6 h interval postoperatively, the ODF8 group had a significantly lower incidence of vomiting when compared with the placebo (P = 0.002) and the IV group (P = 0.044). During the 0-24 h interval postoperatively, ODF4 (P = 0.01) and ODF8 (P = 0.002) groups had a significantly lower incidence of vomiting compared to the placebo group. CONCLUSIONS: Orally disintegrating film of ondansetron is an efficacious, novel, convenient and may be a cost-effective option for the prophylaxis of PONV.